(untitled) (Research, Society and Development, 2022)
Brazil has an abundance of plants that can be used for therapeutic purposes, among them, Jucá, which has anti- inflammatory, antidiarrheal and healing properties. The objective was to evaluate the characteristics of Jucá pods and seeds. Metabolic extracts were prepared for the nutrient content of the fruit as well as the presence of antioxidants, phenolic compounds and flavonoids. Jucá has Boron (2.57 ± 0.15), Copper (0.57 ± 0.16), Iron (11.87 ± 2.14), Manganese (4.93 ± 0.45), Zinc (2.03 ± 0.07), Total Nitrogen (1.03 ± 0.00), Phosphorus (0.12 ± 0.01), Potassium (1.10 ± 0.14), Calcium (0.22 ± 0.03), Magnesium (0.07 ± 0.01) and Sulfur (0.09 ± 0.01). In the evaluation of centesimal composition, it was also verified the dry matter (88.57 ± 0.69) ethereal extract (0.24 ± 0.01), mineral matter (3.17 ± 0.06), crude protein (7.31 ± 0.21), crude fiber (15.25 ± 0.4), ashes (24.6 ± 3.18) and total energy composition (92.38 ± 0.87 Kcal/g). Jucá contains phenolic compounds in tea (12.22 ± 1.04) and extract (142.74 ± 16.59), flavonoids in tea (4.63 ± 0.76) and extract (33.89 ± 4.63) and antioxidants in tea (48.29 ± 5.5) and extract (520.87 ± 57.52). Jucá has a protein, mineral and fiber content. There was a higher concentration of phenolic compounds, flavonoids and antioxidants in the methanolic extract, however, it is through the tea from the parts of the plant that the population uses Jucá.